Corrosion behavior of carbon steel, stainless steel, aluminum and copper upon exposure to biodiesel blended with petrodiesel. (1st July 2021) - Kugelmeier, Cristie Luis; Monteiro, Marcos Roberto; da Silva, Rodrigo; Kuri, Sebastião Elias; Sordi, Vitor Luiz; Della Rovere, Carlos Alberto
Abstract: In this study, the compatibility and corrosion behavior of carbon steel, stainless steel, aluminum and copper in contact with blends composed of biodiesel (consisting of soybean oil, beef tallow and swine lard) and petrodiesel were evaluated. Static immersion tests (total, partial and crevice) and exposure in vapor phase were carried out for 2160 h at 50 °C. Our main findings indicate that fuel blends influence the corrosion behavior, being observed a less corrosive attack on the materials, except for copper that presented an anomalous corrosion behavior, with a clear trend towards lower corrosion rates. Carbon steel and stainless steel in total, partial and crevice tests presented surface morphology with slightly changes, while carbon steel exposed in vapor phase showed corrosive attack. Copper presented the highest corrosion rates in partial (9.5273 μm/y), total (9.1484 μm/y) and crevice (6.6178 μm/y) tests in the B7 blend, respectively; and the lowest corrosion rates in total (0.0547 μm/y) for the B15 blend; in partial (0.4926 μm/y) and crevice (0.0182 μm/y) tests for the B30 blend. Among the materials evaluated, copper showed higher influence on biodiesel oxidative stability. Aluminum exhibited good compatibility and did not show any compound formed on its surface without presenting any corrosion. Graphical abstract: Image 1 Highlights: Corrosion behavior of metallic materials in contact with biodiesel-diesel fuel blends was studied. Biodiesel made of soybean oil, beef tallow and swine lard was used to prepare the blends. Total, partial and crevice immersion tests and exposure in vapor phase were explored. Cu presents anomalous behavior as a function of biodiesel concentration. Biodiesel oxidative stability was greater than 5 h after contact with the materials, but less than 30 min for Cu.